2010
DOI: 10.3758/s13421-010-0048-x
|View full text |Cite
|
Sign up to set email alerts
|

Do object refixations during scene viewing indicate rehearsal in visual working memory?

Abstract: Do refixations serve a rehearsal function in visual working memory (VWM)? We analyzed refixations from observers freely viewing multiobject scenes. An eyetracker was used to limit the viewing of a scene to a specified number of objects fixated after the target (intervening objects), followed by a four-alternative forced choice recognition test. Results showed that the probability of target refixation increased with the number of fixated intervening objects, and these refixations produced a 16% accuracy benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 60 publications
0
64
0
Order By: Relevance
“…It is possible that task demands in the current study may have altered return saccade probability; the need to remember the objects and words in the arrays may have increased the likelihood of making return saccades (cf. Zelinsky et al, 2011), and that fewer return saccades would have been observed in a visual search task where distractor objects do not need to be committed to memory. Even so, any spatial effects of O-IOR should have been detectable in the current study.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that task demands in the current study may have altered return saccade probability; the need to remember the objects and words in the arrays may have increased the likelihood of making return saccades (cf. Zelinsky et al, 2011), and that fewer return saccades would have been observed in a visual search task where distractor objects do not need to be committed to memory. Even so, any spatial effects of O-IOR should have been detectable in the current study.…”
Section: Discussionmentioning
confidence: 97%
“…For example, if return saccades serve as a rehearsal function (e.g., Zelinsky, Loschky, & Dickinson, 2011), then tasks requiring more rehearsal (e.g., memorization) would need a mechanism for making trial-to-trial adjustments to gaze control settings, raising and lowering the criterion to execute a return saccade as warranted by task goals. Implementing such adjustments, however, may be effortful or time consuming and thus may have deleterious effects on performance in switch trials.…”
Section: Discussionmentioning
confidence: 99%
“…And refixation of an object would most likely reflect failure to retain that object robustly in VWM, generating the need to resample the original stimulus. However, such a process could certainly operate in a manner that was functionally similar to a rehearsal mechanism, enabling the sustained, active maintenance of task relevant objects (Zelinsky et al, 2011). Perceptual resampling is particularly applicable within vision, because the visual scene often remains available throughout an extended event (Ballard et al, 1995; O’Regan, 1992), in contrast with auditory-linguistic stimuli that are typically available for only a short duration.…”
Section: Discussionmentioning
confidence: 99%